Lulur bedda lotong rahasia kecantikan wanita suku bugis: Lulur bedda lotong - Aisha; Nur Azila; Annisa Ishaka Ismail; Sapar Sapar; Samsinar Samsinar (Cv. Utility Project Solution, 2023)
Make a useful lotong bedda scrub using spices. This student entrepreneurship and creativity program aims to inspire and motivate students to become entrepreneurs. This program uses input, process (production), output, and evaluation methods. The results obtained from this program are: input, to ensure market conditions we conducted a market survey, interviewed 10 students at Muhammadiyah University of Palopo, conducted a feasibility study of the business to be carried out, selected materials, and provided facilities and infrastructure to support the production process. The process (production) of making bedda lotong scrub begins with providing materials and tools and continues until the lotong bedda scrub is ready to be sold. Output, namely the result of the lotong bedda scrub that can be purchased and used by consumers. And the last is evaluation, this stage is carried out when the production of Bedda Lotong scrubs has been completed, and will check for any deficiencies that make customers feel uncomfortable using the Bedda Lotong scrubs that we produce. The conclusion of the PKM-K program is to use spices to make scrubs that are of sale value and so that the public and students know about the benefits of using scrubs. In addition, it can encourage students to continue doing business by giving them the opportunity to practice and have a comprehensive understanding of the concept of entrepreneurship.